How far are we from the slippery slope? The Laffer curve revisited - Mathias Trabandt; Harald Uhlig (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2006)
The goal of this paper is to examine the shape of the Laffer curve quantitatively in a simple neoclassical growth model calibrated to the US as well as to the EU-15 economy. We show that the US and the EU-15 area are located on the left side of their labor and capital tax Laffer curves, but the EU-15 economy being much closer to the slippery slopes than the US. Our results indicate that since 1975 the EU-15 area has moved considerably closer to the peaks of their Laffer curves. We find that the slope of the Laffer curve in the EU-15 economy is much flatter than in the US which documents a much higher degree of distortions in the EU-15 area. A dynamic scoring analysis shows that more than one half of a labor tax cut and more than four fifth of a capital tax cut are self-financing in the EU-15 economy.
Keywords: E0; E60; H0; 330; Laffer curve; US and EU-15 economy; Steuerpolitik; Steuerbelastung; Arbeit; Kapital; Laffer-Kurve; Neoklassik; Wirtschaftsmodell; USA; EU-Staaten